MATERNAL DIFFICULTIES IN THE PROCESS OF BREASTFEEDING PREMATURES IN THE NEONATAL ICU: AN INTEGRATIVE REVIEW - Oliveira Galdino, Adriana; Eduarda Almeida de Souza, Cicera; Silva Oliveira, Geane; de Lira Silva, Macerlane; Barros de Quental, Ocilma (Health and Society, 2023)
Introduction: Breastfeeding is widely recognized as the gold standard for neonatal nutrition, providing not only essential nutrients but also antibodies and growth factors that are especially vital for premature babies, who often have immature immune systems. It is essential to understand and address these barriers holistically, recognizing the importance of offering adequate support to mothers of premature babies in the NICU, promoting a more positive and beneficial breastfeeding experience for all parties involved. Objective: To highlight the challenges of breastfeeding in the NICU. Methodology: this is an integrative review of the literature, carried out in scientific databases: LILACS, SCIELO and MEDLINE. Results and Discussions: the NICU environment, although crucial for the recovery of premature babies, can be frightening and stressful for mothers. The constant presence of machines and monitors, the strict control of visitors and the intense medical routine can generate anxiety and hinder the feeling of relaxation and intimacy necessary for breastfeeding. These emotional and psychological barriers can impair a mother’s ability to establish and maintain breastfeeding. Another significant set of challenges concerns the physical and technical aspects of breastfeeding in the NICU. Premature babies often do not have the strength or coordination needed to effectively suck breast milk directly from their mother’s breast. Therefore, expressing and administering breast milk through gastric tubes or other methods has become common practice. This can create an environment of discomfort and frustration for mothers, who want to experience breastfeeding in the traditional way. Conclusion: breastfeeding in the NICU is not just about nutrition; It is an act of love and care that strengthens the bond between mother and baby and provides a solid foundation for the child’s future development. Recognizing and addressing maternal difficulties is the first step to ensuring that all mothers of premature babies in the NICU have the opportunity to experience the transformative benefits of breastfeeding and thus promote a healthy and loving start to these precious premature lives.